Analisis Efektivitas Pemberian Insentif Pajak Hiburan Pada Masa Pandemi Covid-19 Di Badan Pengelola Keuangan Daerah Kota Tangerang Tahun 2019-2021 - Agustina, Melina; Agistianto, Jiwa Pribadi; Yanuar, Ryan Dwi (Jurnal Ilmu Administrasi Publik, 2024)
The effectiveness of providing entertainment tax incentives is a method uses to achieve targets in realization. This study aimed to determine how effective the provision of entertainment tax incentives at the Tangerang City Regional Financial Management Agency in 2019-2021. This research method used descriptive qualitative methods through data collection techniques using observations, interviews, documentation. Informants were selected using purposive sampling technique and have expertise in this field. The results of this study indicated that the effectiveness of providing entertainment tax incentives in increasing local revenue at BPKD Tangerang City has not been maximized in its realization so that it does not reach the target in the implementation process there are still obstacles that affect the effectiveness of providing entertainment tax. There are also several ways that can be done to optimize effectiveness, such as by improving online services, improving applications so that there are no errors and maintenance, socializing and educating taxpayers and maintaining local economic sustainability by providing direct support to taxpayers.